The Raven at the ash door - Linde, K. A. (Linde, K. A. Oak & holly cycle, 2026)
Can love survive an unbreakable curse? Kierse McKenna's magic is bound to a man she hates-one who has spent lifetimes fighting the man she loves. To end this binding, Graves-her winter god, her monster-will stop at nothing. He discovers that the only hope of freeing Kierse is to locate a stone relic of legend, rumored to lift any curse. The only problem? The stone has been missing for a century. And the Oak King is on their trail. Now Kierse is trapped at the heart of a centuries-long battle while the rest of the world comes unraveled. The Fae Killer is hunting. The peace with monsters is fracturing. And as the very rules of their myth start to shift, escaping the Oak King's hold may demand more than stolen artifacts and clever heists. For Kierse and Graves, it may mean risking the only thing they have left to lose.